Educação e história: a escola estadual Maria Iracema Munhoz, em São Bernardo do Campo, desde 1890 a 1930 - Franssatto, Rosa de Fátima Moraes (2007)
This research, of qualitative nature of ethnographic nature, is directed to the decentralization educational policies, which has its field of action in the micro universe of the school. In this context, the role of the school boards is highlighted, among them the Class and Grade Council, as this has been materializing as one of the spaces that most favors the participation of different segments of the school, becoming a determining factor for the quality of the democratization of the school. school management and teaching-learning. The research was developed in three moments: 1) analysis of school documentation; 2) observations in a state school institution of the public school of São Bernardo do Campo and 3) open and semi-structured interviews with parents, student teachers and managers who provided support to make considerations about the practices performed during the Class Councils and Series. (AU)